Strategi Kontra-Terorisme Hard Approach dan Soft Approach di Indonesia - I Putu Hadi Pradnyana (Frequency of International Relations (FETRIAN), 2022)
This research examines the dynamics of counter-terrorism policies in Indonesia from the Old Order (Orde Lama) era to the current period. Terrorist attacks have been a threat to Indonesia's national security since the beginning of the nation's independence. The government is required to counter terrorism through a series of effective policies. This research uses descriptive qualitative method with literature study. The results of the research obtained are that the pattern of countering terrorism in Indonesia is divided into two types of approaches, the hard approach and the soft approach. The hard approach method refers to the use of armed forces against terror organizations. The soft approach method prioritizes integrated and comprehensive actions in dealing with the problem of radicalism starting from the root of the problem. The hard approach was more used in the early era of independence until the New Order. Meanwhile, the soft approach has been massively used since the establishment of the National Counterterrorism Agency (BNPT) in 2010 until now. Indonesia's policies in the counter-terrorism strategy are then divided into three, namely strengthening counter- terrorism regulations, making programs to prevent terrorism crimes, and increasing the capacity of anti-terror organizations.